A dose homogeneity and conformity evaluation between ViewRay and pinnacle-based linear accelerator IMRT treatment plans - Saenz, Daniel L. (Medknow Publications & Media Pvt Ltd, 2014)
ViewRay, a novel technology providing soft-tissue imaging during radiotherapy is investigated for treatment planning capabilities assessing treatment plan dose homogeneity and conformity compared with linear accelerator plans. ViewRay offers both adaptive radiotherapy and image guidance. The combination of cobalt-60 (Co-60) with 0.35 Tesla magnetic resonance imaging (MRI) allows for magnetic resonance (MR)-guided intensity-modulated radiation therapy (IMRT) delivery with multiple beams. This study investigated head and neck, lung, and prostate treatment plans to understand what is possible on ViewRay to narrow focus toward sites with optimal dosimetry. The goal is not to provide a rigorous assessment of planning capabilities, but rather a first order demonstration of ViewRay planning abilities. Images, structure sets, points, and dose from treatment plans created in Pinnacle for patients in our clinic were imported into ViewRay. The same objectives were used to assess plan quality and all critical structures were treated as similarly as possible. Homogeneity index (HI), conformity index (CI), and volume receiving <20% of prescription dose (DRx) were calculated to assess the plans. The 95% confidence intervals were recorded for all measurements and presented with the associated bars in graphs. The homogeneity index (D5/D95) had a 1-5% inhomogeneity increase for head and neck, 3-8% for lung, and 4-16% for prostate. CI revealed a modest conformity increase for lung. The volume receiving 20% of the prescription dose increased 2-8% for head and neck and up to 4% for lung and prostate. Overall, for head and neck Co-60 ViewRay treatments planned with its Monte Carlo treatment planning software were comparable with 6 MV plans computed with convolution superposition algorithm on Pinnacle treatment planning system.